Leveraging Antimicrobial Stewardship in the Emergency Department to Improve the Quality of Urinary Tract Infection Management and Outcomes. (2nd May 2018) - Jorgensen, Sarah C J; Yeung, Samantha L; Zurayk, Mira; Terry, Jill; Dunn, Maureen; Nieberg, Paul; Pallares, Jean; Wong-Beringer, Annie
Abstract: Background: The complex and fast-paced emergency department (ED) practice setting presents unique challenges that demand a tailored approach to antimicrobial stewardship. In this article, we describe the strategies applied by 1 institution's antimicrobial stewardship program (ASP) that were successful in improving prescribing practices and outcomes for urinary tract infection (UTI) in the ED. Methods: Core strategies included pre-implementation research characterizing the patient population, antimicrobial resistance patterns, prescribing behavior, and morbidity related to infection; collaboration across multiple disciplines; development and implementation of a UTI treatment algorithm; education to increase awareness of the algorithm and the background and rationale supporting it; audit and feedback; and early evaluation of post-implementation outcomes. Results: We observed a rapid change in prescribing post-implementation with increased empiric nitrofurantoin use and reduced cephalosporin use ( P < .05). Our elevation of nitrofurantoin to firstline status was supported by our post-implementation analysis showing that its use was independently associated with reduced 30-day return visits (adjusted odds ratio, 0.547; 95% confidence interval, 0.312–0.960). Furthermore, despite a shift to a higher risk population and a corresponding decrease in antimicrobial susceptibility rates post-implementation, the preferential use of nitrofurantoin did not result in higher bug-drug mismatches while 30-day return visits to the ED remained stable. Conclusions: We demonstrate that an outcomes-based ASP can impart meaningful change to knowledge and attitudes affecting prescribing practices in the ED. The success of our program may be used by other institutions as support for ASP expansion to the ED.